Genetic influence of CYP2D6 on pharmacokinetics and acute subjective effects of LSD in a pooled analysis - Vizeli, Patrick; Straumann, Isabelle; Holze, Friederike; Schmid, Yasmin; Dolder, Patrick C.; Liechti, Matthias E. (Scientific reports, 2021)
Lysergic acid diethylamide (LSD) is a classic psychedelic substance that is used recreationally and investigated in psychiatric research. There are no pharmacogenetic studies on LSD. In vitro metabolic studies indicate that several cytochrome P450 (CYP) isoforms (e.g., CYP2D6, CYP1A2, and CYP2C9) are involved in LSD metabolism, but in vivo data are scarce. The present study examined the influence of genetic polymorphisms of CYP genes on the pharmacokinetics and acute effects of LSD in healthy subjects. We identified common genetic variants of CYPs (CYP2D6, CYP1A2, CYP2C9, CYP2C19, and CYP2B6) in 81 healthy subjects who were pooled from four randomized, placebo-controlled, double-blind Phase 1 studies. We found that genetically determined CYP2D6 functionality significantly influenced the pharmacokinetics of LSD. Individuals with no functional CYP2D6 (i.e., poor metabolizers) had longer LSD half-lives and approximately 75% higher parent drug and main metabolite 2-oxo-3-hydroxy LSD area-under-the-curve blood plasma concentrations compared with carriers of functional CYP2D6. Non-functional CYP2D6 metabolizers also exhibited greater alterations of mind and longer subjective effect durations in response to LSD compared with functional CYP2D6 metabolizers. No effect on the pharmacokinetics or acute effects of LSD were observed with other CYPs. These findings indicate that genetic polymorphisms of CYP2D6 significantly influence the pharmacokinetic and subjective effects of LSD. Given the potential therapeutic use of psychedelics, including LSD, the role of pharmacogenetic tests prior to LSD-assisted psychotherapy needs to be further investigated.